1999
DOI: 10.1099/00221287-145-11-3013
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of the phase variation repertoire of lipopolysaccharide immunotypes in Neisseria meningitidis The GenBank accession number for the sequence reported in this paper is U65788.

Abstract: Neisseria meningitidis strains express a diverse range of lipopolysaccharide (LPS) structures that have been classified into 12 immunotypes. A feature of meningococcal LPS is the reversible, high-frequency switching of expression (phase variation) of terminal LPS structures. A number of studies are strongly suggestive of a key role for these terminal structures, and their phase-variable expression, in pathogenesis. In a previous study, a locus of three LPS biosynthetic genes, lgtABE, involved in the biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
113
1
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 18 publications
3
113
1
3
Order By: Relevance
“…Whereas capsules prevent desiccation during open-air transmission and make the bacteria less vulnerable to phagocytosis in the blood, they also reduce the likelihood of N. meningitidis invading the cells of the epithelia (Hammerschmidt et al 1996;de Vries et al 1996). Sialylated LPS play a dual role in evading host immunity in the blood and facilitating entry into epithelial cells (de Vries et al 1996;Jennings et al 1999 L8 LPS are favoured in the epithelia and sub-epithelia. In addition, in the blood, capsulated N. meningitidis with assembled pili and L3, L9 and L7 LPS have an advantage.…”
Section: Overviewmentioning
confidence: 99%
“…Whereas capsules prevent desiccation during open-air transmission and make the bacteria less vulnerable to phagocytosis in the blood, they also reduce the likelihood of N. meningitidis invading the cells of the epithelia (Hammerschmidt et al 1996;de Vries et al 1996). Sialylated LPS play a dual role in evading host immunity in the blood and facilitating entry into epithelial cells (de Vries et al 1996;Jennings et al 1999 L8 LPS are favoured in the epithelia and sub-epithelia. In addition, in the blood, capsulated N. meningitidis with assembled pili and L3, L9 and L7 LPS have an advantage.…”
Section: Overviewmentioning
confidence: 99%
“…These genes are often referred to as contingency loci . Phase variable expression has been experimentally demonstrated for surface antigens such as opacity proteins, lipopolysaccharides, capsular polysaccharides, pili, haemoglobin receptors, PorA and Opc outer-membrane proteins, a putative protease and the NadA adhesin (de Vries et al, 1996;Jennings et al, 1998Jennings et al, , 1999Hammerschmidt et al, 1996;Jonsson et al, 1991;Lewis et al, 1999;Richardson & Stojiljkovic,1999;van der Ende et al, 2000;Sarkari et al, 1994;Martin et al, 2003). We recently showed that 47 genes were likely to be regulated by such a mechanism in N. meningitidis strain MC58 (Martin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…One important example is LPS phase variation by means of contingency loci that allows these bacteria to express different LPS molecules after every generation, enhancing their ability to survive and escape host immune cell recognition (23,24,27). Thus, strong selective pressure from the immune system during bacterial invasion is believed to be the driving force of LPS variation among these bacteria.…”
mentioning
confidence: 99%
“…Bacterial survival within the host's blood stream depends on the ability to escape the innate and adaptive immune systems, and H. influenza and N. meningitidis both have multiple genes under control of phase variation that result in antigenic variants arising every generation, allowing for immune evasion (20)(21)(22)(23)(24)(25)(26)(27)(28). One important example is LPS phase variation by means of contingency loci that allows these bacteria to express different LPS molecules after every generation, enhancing their ability to survive and escape host immune cell recognition (23,24,27).…”
mentioning
confidence: 99%